A Porous Framework as a Variable Chemosensor: From the Response of a Specific Carcinogenic Alkyl‐Aromatic to Selective Detection of Explosive Nitroaromatics. Issue 43 (18th July 2018) - Xue, Hui; Song, Danhua; Liu, Caiping; Lyu, Guangxun; Yuan, Daqiang; Jiang, Feilong; Chen, Qihui; Hong, Maochun
Abstract: Selective probing of one molecule from one class of similar molecules is highly challenging due to their similar chemical and physical properties. Herein, a novel metal–organic frameworkFJI ‐H15 with flexible porous cages has been designed and synthesized, which can specifically recognize ethylbenzene with ultrahigh enhancement efficiency from a series of alkyl‐aromatics, in which an unusual size‐dependent interaction has been found and proved. It can also selectively detect phenolic‐nitroaromatics among a series of nitroaromatics based on energy transfer and electrostatic interactions. Such unusual specificity and variable mechanisms responding to different types of molecules have not yet been reported, which will provide a new strategy for the development of more effective chemosensors based on MOFs for probing small structural differences in molecules. Abstract : Detecting harmful aromatics : A metal–organic framework with flexible porous cages has been designed and synthesized, which can specifically recognize ethylbenzene with ultrahigh enhancement efficiency from a series of alkyl‐aromatics (see scheme).